Impact of Gestational Age on Nuchal Fold Thickness in the Second Trimester. (1st April 2014) - Singh, Chanchal; Biswas, Arijit
Abstract : Objectives: The purpose of this study was to establish gestational age (GA)–specific nomograms for nuchal fold thickness between 16 and 24 weeks. Methods: This retrospective cross sectional study included 32, 207 women who underwent a second‐trimester anomaly scan at the Fetal Care Center of National University Hospital from January 2005 to April 2011. Nomograms were plotted for nuchal fold thickness at each gestation to study its variation with GA. Results: Nuchal fold thickness increased with GA in a linear manner from 3.13 ± 0.68 mm (mean ± SD) at 16 weeks to 5.08 ± 0.76 mm at 24 weeks. The 95th percentile measurement at 24 weeks remained less than 6 mm. Conclusions: A threshold of 6 mm appears to be appropriate for the diagnosis of a thick nuchal fold even for gestations between 20 and 24 weeks.